2012
DOI: 10.1242/jcs.094946
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of myosin X movements by its cargos, DCC and neogenin

Abstract: SummaryMyosin X (Myo X), also known as MYO10, is an unconventional actin-based motor protein that plays an important role in filopodium formation. Its intra-filopodia movement, an event tightly associated with the function of Myo X, has been extensively studied. However, how the motor activity of Myo X and the direction of its movements are regulated remains largely unknown. In our previous study, we demonstrated that DCC (for 'deleted in colorectal carcinoma') and neogenin (neogenin 1, NEO1 or NGN), a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
(57 reference statements)
0
21
1
Order By: Relevance
“…Myo10 can bind to the netrin receptors DCC and neogenin (6,23,28,29) and is required to localize DCC to neurites (28). However, in this study, outgrowth was not stimulated by any exogenous guidance cue or growth factor, indicating that Myo10 is required for baseline axon outgrowth independent of external cues.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Myo10 can bind to the netrin receptors DCC and neogenin (6,23,28,29) and is required to localize DCC to neurites (28). However, in this study, outgrowth was not stimulated by any exogenous guidance cue or growth factor, indicating that Myo10 is required for baseline axon outgrowth independent of external cues.…”
Section: Discussioncontrasting
confidence: 56%
“…Myo10 localizes to the tips of filopodia (2-6), moves within filopodia (6 -10), and induces the formation of filopodia (4,6,7,10,11). Given the importance of filopodia in neuronal development, particularly in axon outgrowth and branching (12)(13)(14)(15), Myo10 is likely to have critical functions in neuronal development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myo10 also binds to transmembrane netrin receptors DCC and neogenin, and disruption of these interactions results in defects of axonal projection and path finding [5,7,44]. These cargoes have been shown to differentially regulate Myo10 activity and induction of filopodia formation, with DCC enhancing basal filopodia elongation and neogenin promoting dorsal filopodia growth [45]. VE-cadherin and N-cadherin are Myo10 cargoes that function in the formation of early endothelial cell-cell contacts and neuronal radial migration, respectively [46,47].…”
Section: Myth4-ferm Myosin Cargoes and Physiological Functionsmentioning
confidence: 99%
“…Multiple studies have demonstrated that MSCs inhibit effector T cell proliferation and cytokine release through mechanisms that are cell-contact-dependent (PD-L1, Augello et al, 2005; B7-H4, Xue et al, 2010; ICAM1; VCAM1, Ren et al, 2010) and contact-independent (IDO, Ge et al, 2010; PGE 2 , Najar et al, 2010; Duffy et al, 2011b; HLA-G, Selmani et al, 2009; TGFβ, Liu et al, 2012; galectins, Sioud, 2011). In vivo models have shown that MSCs have an indirect effect on T cell activation by inhibition of maturation of DCs.…”
Section: Immunomodulatory Effect Of Mscs In Transplantationmentioning
confidence: 99%